Proceedings of the 8th Economics &Amp; Finance Conference, London 2017
DOI: 10.20472/efc.2017.008.005
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Functioning of the Bitcoin System – User Assessment

Abstract: Abstract:Bitcoin is a system created to service micro-payments in e-commerce, as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Piotrowska and Piotrowski [11] investigate the main weaknesses limiting the functioning of the bitcoin system, and its use in payments in particular in a survey conducted among Polish bitcoin users. They identified these threats: the speculative nature of bitcoin, the lack of adequate awareness in society which would allow for a widespread use of the innovation, potentially too strict regulation of the cryptocurrencies market or its banning.…”
Section: Usage Of Cryptocurrenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Piotrowska and Piotrowski [11] investigate the main weaknesses limiting the functioning of the bitcoin system, and its use in payments in particular in a survey conducted among Polish bitcoin users. They identified these threats: the speculative nature of bitcoin, the lack of adequate awareness in society which would allow for a widespread use of the innovation, potentially too strict regulation of the cryptocurrencies market or its banning.…”
Section: Usage Of Cryptocurrenciesmentioning
confidence: 99%
“…Piotrowska and Piotrowski [11] also presented threats to the functioning of the system which, in their opinion, are of biggest importance at the moment: the existence of intermediaries, the lack of systemic incentives addressed to bitcoin merchants, growing costs and payment processing time.…”
Section: Usage Of Cryptocurrenciesmentioning
confidence: 99%
“…Similarly, the Adreianova et al study sent out survey invitations to members of LocalBitcoin, a peer-to-peer bitcoin marketplace website [8]. The Piotrowska 2017 study used Polish websites, including forums, blogs, news services, and social media for survey invitations [18]. In some cases, existing surveys were adapted, such as one taken from Blockchain Capital's 2017 Bitcoin research at Erzincan Binali Yıldırım University [19].…”
Section: Recruitment Findingsmentioning
confidence: 99%
“…Beyond investments, sending money internationally was a recurrent theme among participants across these studies [12][13][14]18]. Andreianova et al [8] found that 9.7% or 5206 respondents use bitcoin for remittance and cited it as the second most common option after traditional bank transfers.…”
Section: International Transfersmentioning
confidence: 99%
“…After special software has been installed on the miner's computer, the task involves solving a certain inequality using a Secure Hash Algorithm, known as SHA-256. The solution is found by the trial-and-error method (Piotrowska, 2018;Ross, 2017;Dhillon, Metcalf, & Hooper, 2018), and is equivalent to the creation of a new block.…”
Section: Stages In the Development Of Blockchainmentioning
confidence: 99%